Women and politics - Burrell, Barbara C., 1947-, author.
1 online resource (viii, 268 pages)
Keywords: "This textbook for courses on women and politics thematically integrates two profound historical developments focusing on women's political participation in contemporary public life in the United States. The second wave of women's rights activism has now spanned a half century producing a revolution in women's presence and influence in the public realm of American life. Over the course of this same era, however, a second phenomenon of rising economic inequality has also dramatically changed the American landscape. Burrell's text uniquely examines the effect of the age of inequality on women's advancement toward economic and political equality and in turn how policy initiatives of the women's movement have addressed inequality issues. Students will come to better understand what's at stake in the politics and policy issues from the women's rights movement to the "war on women" debate.Explaining a diverse set of issues and viewpoints, Burrell brings a fresh approach to the engagement of women in the public realm over the past half century. Framing this activism in the great economic divide of the same time period provides a thought-provoking, challenging, and broad thematic approach to this history. The text chronicles the many diverse types of actions women have taken in the contemporary era to achieve gender equity, empowerment, and a greater public voice. Women'"both liberal feminist and conservative'" have run for and been elected to positions of leadership at all levels of government. Women have formed organizations to lobby for equity in employment and education, in the military and to promote reproductive rights. They have engaged in unconventional political activities marching against and protesting the actions and policies of economic corporations and governmental institutions. Women with few economic resources have joined together to challenge local power structures. In addition to efforts to improve the lives and status of women in the United States, nongovernmental organizations (NGOs) have formed to promote global women's rights. Readers of this text will gain a great appreciation of the multiple political voices of American women and the challenges to continued unequal voices."--Provided by publisher.